Sex Dimorphisms in Ischemic Stroke: From Experimental Studies to Clinic - Jiang, Ming; Ma, Cheng; Li, Haiying; Shen, Haitao; Li, Xiang; Sun, Qing; Chen, Gang (Frontiers in Neurology, 2020)
Sex dimorphisms are important factors influence the outcomes after ischemic stroke, which include basic health status, cerebrovascular anatomy, hormone levels, unique factors such as pregnancy and menopause. It is widely recognized that male and female respond differently to stroke. Hence, there is increasing requirement to get a more comprehensive understanding of sex-based factors to stroke. This review focus on the sex-specific mechanisms in response to stroke based on experimental studies and highlights the recent findings in clinical studies including sex-differential evaluation and outcomes of stroke. Sex-based personalized medicine should be promising in stroke therapies.